Gene Expression in Amnion-Derived Cells Cultured on Recombinant Laminin 332—A Preliminary Study - Skowron-Kandzia, Katarzyna; Tomsia, Marcin; Koryciak-Komarska, Halina; Plewka, Danuta; Wieczorek, Patrycja; Czekaj, Piotr (Frontiers in Medicine, 2021)
Human amniotic cells (hAC) exhibit characteristics of undifferentiated cells and immunomodulatory properties. Recognition of the relationship between amniotic cells and components of the extracellular matrix is an important condition for their ex vivo preparation and further successful clinical application in regenerative medicine and transplantology. Laminin 332 (LN-332), as a natural component of the basement membrane of amniotic epithelial cells and a ligand for integrin receptors, may strongly influence the phenotype and fate of amniotic cells. We investigated the impact of recombinant LN-332 on hAC viability and expression of markers for pluripotency, early differentiation, adhesion, and immunomodulatory properties. During 14 days of culture, hAC were quantified and qualified by light microscopy, immunohistochemistry, immunocytochemistry, and flow cytometry. Gene expression was assessed with real-time polymerase chain reaction (RT-PCR) arrays and compared with differentiated cells originated from the three germ layers. LN-332 caused an over twofold increase in the total number of hAC, accompanied by a 75% reduction of SSEA-4-positive cells and an increase in HLA-ABC-positive cells. In particular, we observed that the presence of laminin 332 in the medium of a short-time culture modifies the effect of culture duration on hAC, enhancing time-dependent inhibition of expression of certain genes, including pluripotency and differentiation markers, laminin 332 subunits (which may be part of self-regulation of LN-332 synthesis by amniotic cells), and integrins. These changes observed in hAC were more distinct with respect to differentiated mesenchymal cells, resulting in more comparable phenotypes than those represented by differentiated endo- and ectodermal cells. We concluded that laminin 332 present in the culture medium influences to a certain extent proliferation, adhesion, and differentiation of amniotic cells in culture.